Vector Approach of Collision Prognosis of Mobile Robots - Bartkevicius, S.; Jakas, Z.; Sarkauskas, K. (Elektronika ir Elektrotechnika, 2012)
A method to detect potential collision of moving robots, operating in the same environment, is discussed. Criteria of collision is formulated – two robots will collide, if the angle between vector of difference of speeds and difference of vectorial distances of robots to crossing point of linear traces is less then half of the visibility angle, from position of one of robots, of the circle with diameter equal to sum of diameters of circles involving robots, placed in position of other robot. It is determined, that usage of this criteria allows to check possible collisions only in start position of robots or when one of them changes direction of movement. Ill. 4, bibl. 4 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.121.5.1655